TOXICITY TEST OF ORANGE BENALOY LEAVES ETHANOL (Scurrula ferrugenia (Jack) Danser) ON Artemia salina L. Shrimp LARVA AND IDENTIFICATION OF SECONDARY METABOLITE COMPOUNDS - Yulandari, N. K. N.; Rita, W. S.; Rustini, N. L. (Jurnal Kimia (Journal of Chemistry), 2023)
Benalu jeruk, Scurrula ferrugenia (Jack) Danser, dapat dimanfaatkan untuk pengobatan kanker atau sitotoksik. Penelitian ini bertujuan untuk mengetahui toksisitas ekstrak etanol daun benalu jeruk (Scurrula ferruginea (Jack) Danser) terhadap larva udang Artemia salina serta kandungan golongan senyawa metabolit sekunder dengan metode skrining fitokimia. Ekstraksi dilakukan dengan metode maserasi dan partisi, Uji toksisitas dilakukan dengan metode Brine Shirmp Lethality Test (BSLT), dan skrining fitokimia dilakukan dengan menggunakan beberapa pereaksi pendekteksi golongan senyawa. Maserasi 1 kg serbuk daun benalu jeruk menghasilkan ekstrak pekat etanol sebesar 49,74 gram. Proses partisi 10 gram ekstrak pekat etanol menghasilkan 5,3838 gram ekstrak pekat n-heksana, 2,2239 gram ekstrak pekat etil asetat, 1,3012 gram ekstrak pekat n-butanol dan 1,0911 gram ekstrak air. Hasil uji toksisitas ekstrak etanol, n-heksana, etil asetat, n-butanol dan air secara berturut-turut dengan nilai LC50 162,7565; 83,3017; 147,0026; 660,2279; dan 921, 6679 ppm. Skrining fitokimia menunjukkan hasil positif terhadap metabolit sekunder alkaloid, saponin, steroid, flavonoid, dan tanin. Kata kunci: benalu jeruk (Scurrula ferrugenia (Jack) Danser, toksisitas, uji fitokimia ABSTRACT The citrus parasite, Scurrula ferrugenia (Jack) Danser, can be used for the treatment of cancer or cytotoxic. This study aimed to determine the toxicity of the ethanol extract of citrus parasite leaves (Scurrula ferruginea (Jack) Danser) against shrimp larvae of Artemia salina and the content of secondary metabolite compounds using phytochemical screening methods. The extraction was carried out by the maceration and partitioning methods, the toxicity test by the Brine Shrimp Lethality Test (BSLT) and phytochemical screening by using several detection reagents. Maceration of 1 kg of citrus parasite leaves yielded a concentrated ethanol extract of 49.74 grams. The partition process of 10 grams of concentrated ethanol extract produced 5.3838 grams of concentrated n-hexane extract, 2.2239 grams of concentrated ethyl acetate extract, 1.3012 grams of concentrated n-butanol extract and 1.0911 grams of water extract. The toxicity test for ethanol, n-hexane, ethyl acetate, n-butanol and water extracts resulted in LC50 values ??of 162.7565; 83.3017; 147.0026; 660.2279; and 921.6679 ppm, respectively. Phytochemical screening showed positive results for secondary metabolites of alkaloids, saponins, steroids, flavonoids, and tannins. Keywords: citrus parasite (Scurrula ferrugenia (Jack) Danser, toxicity, phytochemical test